Use of Statistical Correlation Analysis in the Study of Road Accidents: Array - Amortila, Valentin; Mereuta, Elena; George Balasoiu, George Balasoiu; Veresiu, Silvia (Journal of Danubian Studies and Research, 2021)
This paper performs a statistical analysis of the dependency relationships between processes and phenomena and focuses on highlighting the main causes of accidents. As the number of vehicles increased, so did the number of accidents. When we talk about the road transport system, we must not exclude the fact that there will always be road accidents due to unpredictable causes (vehicle failures) or foreseeable (infrastructure, reckless driving). All these causes can be amplified by a series of conditions such as day or night, road category, but also by the manner and nature of accidents (between vehicles, between vehicle and pedestrian, etc.). Using the analysis of the Pearson correlation between the codings, the nature, the mode and the place of accidents in Romania, it was highlighted that the most prone to accidents at night are new vehicles and "used" vehicles are responsible for accidents in localities.